CHARACTERIZATION AND EVALUATION OF SOME PEACH [PRUNUS PERSICA (L.) BATSCH.] ACCESSIONS FOR FRUIT QUALITY TRAITS - SUMAN BODH,; DINESH SINGH,; NIRMLA CHAUHAN, (The Bioscan, 2020)
The present investigation entitled “Characterization and evaluation of some peach [Prunus persica (L.) Batsch.] accessions for fruit quality traits” was carried out in the field gene bank of National Bureau of Plant Genetic Resources, Regional Station Phagli, Shimla during 2017-2018. Sixteen peach genotypes namely Shan-i-Punjab, Kanto-5, Fertilia, Yum Yong, Flordasun, Summerglo, Suncoast, FlordaBelle, Ambri, Early Redhaven, Okubo, Early Amber, Fire Prince, Belle of Georgia, Hale Haven and Nishiki were evaluated for their fruit characters. Maximum fruit length (96.95 mm) and fruit diameter (88.45 mm) was recorded in Summerglo, whereas mini- mum fruit length (53.36 mm) and fruit diameter (56.00 mm) was recorded in Shan-i-Punjab and Nishiki respec- tively. Heaviest fruits were found in Suncoast (203.83 g) and lightest fruits were observed in Ambri (72.33 g). Fruit firmness varied from 2.05 kg/cm2 in Shan-i-Punjab to 6.56 kg/cm2 in Hale Haven. Maximum pulp/stone ratio (43.39) was found in Flordasun and minimum (8.87) in Hale Haven. TSS content of fruit was maximum (13.43oB) in FlordaBelle and minimum (8.10oB) in Ambri. Titratable acidity was maximum (1.64%) in Summerglo and minimum (0.20%) in Belle of Georgia. Total sugars were maximum (10.53%) in Fertilia and minimum (6.25%) in Belle of Georgia.